APLIKASI PEMESANAN JASA BARBERSHOP BERBASIS ANDROID - Mustapa, Muhammad Syarif; Suhada, Sitti; Kaluku, Moh Ramdhan Arif; Zakaria, Alfian (Gorontalo State University, 2021)
Nowadays, the barbershop business has grown rapidly and ts widely established in Gorontalo City. The increasing number of barbershop today has highly required the availability of information about barbershop service. The available information needed is the service provided in the barbershop, the pricelist of service, and the profile of the barbershop. The information facilitates the customer to obtain information regarding the barbershop that is suitable for the customer's desires. The research aims to create a barbershop service order app to facilitate the customer in gaming information about the desired barbershop. The method used in this research is the Prototype method. This research produces an android-based information system that can facilitate the barbershop customer in selecting the barbershop as customer desire and still meet the customers' appearance requirements. Keywords: Barbershop, Prototype, Android